Pengaruh Penilaian Esai Terhadap Pencapaian Kompetensi Siswa Pada Pembelajaran IPA: Tinjauan Pustaka - Fleony Dea Amanda; Utari Prisma Dewi; Fatni Mufit; Festiyed Festiyed (Jurnal Penelitian Pendidikan IPA, 2023)
The low scores of Pisa and TIMSS Indonesia show that students' abilities are still weak in 3 categories, namely linguistic literacy, scientific literacy, and mathematical literacy. To measure how far the achievement of student competence can be used assessment essay. Therefore this study aims to see the effect of essay assessment on students' competency achievement in science learning. This study used the literature review method through searches on Google Scholar and ERIC with the keywords "student competency achievement", "Essay Assessment", and "scoring". As research subjects, 16 articles were used which had been extracted from 1000 articles in national journals and international journals between 2019 and 2023. The results showed that the use of assessment essays based on educational level, namely at the high school level had a percentage of 62.5% while at the university level has a percentage of 60%. Furthermore, based on the material, it can be seen that the percentage of using assessment essays in biology and physics subjects obtained a percentage of 60%. So it can be concluded that Essay Assessment has an influence on the Achievement of Student Competence in Science Learning.